IMPLEMENTATION OF CONTINUOUS INTEGRATION/CONTINUOUS DEPLOYMENT TO AUTOMATE COMPUTER NETWORK INFRASTRUCTURE CONFIGURATION MANAGEMENT - Hariyadi, I Putu; Raisul Azhar; Heroe Santoso; Khairan Marzuki; I Made Yadi Dharma (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2023)
Computer network infrastructure is one of the supporting components for smooth operations for companies that utilize Information and Communication Technology (ICT). Companies are required to continue to innovate to continue to grow so it requires various adjustments, including changes to the policy configuration of computer network infrastructure. Implementation of configuration changes to computer network infrastructure if done manually will be inefficient and ineffective. In addition, it is prone to errors as a result of human error resulting in downtime. The application of Continuous Integration/Continuous Deployment (CI/CD) can be a solution to overcome these problems. This study analyzes the implementation of CI/CD on network infrastructure which is simulated using the PNETLab and GitLab CI/CD tools as well as Ansible Configuration Management. Based on the tests conducted five times, it can be concluded that the Ansible Playbook that has been created and integrated with the GitLab CI/CD pipeline can be used to automate configuration management of MikroTik-based network infrastructure that is simulated in PNETLab. CI/CD can speed up the implementation of configuration changes on network devices through an automated process. Testing additional configurations on the test network takes an average of 82.6 seconds. Meanwhile, on the production network, it takes an average of 80.2 seconds. On the other hand, testing the configuration deletion on the test network takes an average of 56.6 seconds. Meanwhile, on the production network, the average is 54.4 seconds. In addition, the application of CI/CD can minimize errors because before the configuration is applied to the production network, the configuration is tested first on the test network automatically. Application of the configuration to the production network is carried out only if testing of the configuration on the test network is successful. The CI/CD mechanism can improve the performance and reliability of computer network infrastructure.